Mechanisms of evolutionary change in structural plumage coloration among bluebirds (Sialia spp.) - Shawkey, Matthew D (The Royal Society, 2006)
Combinations of microstructural and pigmentary components of barbs create the colour displays of feathers. It follows that evolutionary changes in colour displays must reflect changes in the underlying production mechanisms, but rarely have the mechanisms of feather colour evolution been studied. Among bluebirds in the genus Sialia, male rump colour varies among species from dark blue to light blue while breast colour varies from blue to rusty. We use spectrometry, transmission electron microscopy and Fourier analysis to identify the morphology responsible for these divergent colour displays. The morphology of blue rump barbs is similar among the three species, with an outer keratin cortex layer surrounding a medullary ‘spongy layer’ and a basal row of melanin granules. A spongy layer is also present in blue breast barbs of mountain bluebirds Sialia currucoides and in rusty breast barbs of western Sialia mexicana and eastern bluebirds Sialia sialis. In blue barbs melanin is basal to the spongy layer, but is not present in the outer cortex or spongy layer, while in rusty barbs, melanin is present only in the cortex. The placement of melanin in the cortex masks expression of structural blue, creating a rusty display. Such shifts in microstructures and pigments may be widespread mechanisms for the evolutionary changes in the colours of feathers and other reflective structures across colourful organisms.